Prevalence of low back pain and associated risk factors amongst adult patients presenting to a Nigerian family practice clinic, a hospital-based study - Adetola M. Ogunbode; Lawrence A. Adebusoye; Temitope O. Alonge (AOSIS, 2013)
Background: Low back pain (LBP) is a common health problem with concomitant disability which has assumed a public health importance in our setting. Objectives: The aim of this study was to determine the prevalence of LBP and associated risk factors amongst adult patients attending the General Outpatients' Clinic of the UniversityCollege Hospital in Ibadan, Nigeria. Method: This was a cross-sectional study of 485 respondents. A semi-structured questionnaire was used to obtain information on socio-demography, lifestyle, occupation and other riskfactors associated with LBP. Results: There were 288 (59.4%) female and 197 (40.6%) male respondents. The point prevalence of LBP was 46.8%. Occupational activities, previous back injury and tobacco smoking were significant associated factors for the total population. For the female respondents, logisticregression analysis showed that a waist circumference of 88 cm or more, dysmenorrhea,previous back injury and being engaged in an occupation were the most significant factors associated with LBP. However, previous back injury was the most significant factor associatedwith LBP for the male respondents. Conclusion: The prevalence of LBP amongst adult patients in our setting is high, with preventable and treatable predisposing factors. Public health efforts should be directed at educating people on occupational activities and lifestyle habits.